Eco-Friendly Concept Training for MSMEs in Tanjung Rejo Mangrove Tourism Village, Deli Serdang - Indra, Febryola; Sitorus, Nova Bernedeta; Maleachi, Sandra (Yayasan Kawanad, 2025)
Climate change, environmental degradation, and ecosystem destruction demand the adoption of eco-friendly practices in economic activities. Beyond environmental benefits, such practices enhance economic competitiveness, particularly for Micro, Small, and Medium Enterprises (MSMEs). Tanjung Rejo Mangrove Tourism Village in Medan Belawan exemplifies the integration of sustainable tourism with mangrove ecosystem conservation and local economic empowerment through homestays, tour guides, and environmentally-based products. This study evaluates the effectiveness of eco-friendly training for 30 local MSMEs using participatory methods with pre-test and post-test instruments. Results indicate significant improvements across ten indicators (25%-56%), notably in production waste management (56%) and consumer awareness of eco-friendly products (45%). The training successfully catalyzed behavioral transformation toward sustainable business practices, yielding dual impacts on ecosystem preservation and MSME economic competitiveness. Findings demonstrate that structured capacity-building programs can drive collective environmental awareness while strengthening local economies. Recommendations include developing advanced training modules, fostering multi-sector collaboration, and establishing incentive systems for MSMEs consistently implementing eco-friendly practices.